Optimizing care of your patients with COPD - Garvey C (Dove Medical Press, 2014)
Chris Garvey,1 Nicola A Hanania,2 Pablo Altman3 1Seton Pulmonary and Cardiac Rehabilitation, Daly City, CA, USA; 2Asthma Clinical Research Center, Section of Pulmonary, Critical Care and Sleep Medicine, Baylor College of Medicine, Houston, TX, USA; 3Mylan Specialty LP, Basking Ridge, NJ, USA (formerly) Abstract: Chronic obstructive pulmonary disease (COPD) is now the third-leading cause of death in the US. The primary risk factor for COPD is smoking. COPD is underdiagnosed, and spirometry, the main method for its diagnosis, is underutilized. Nurses can play an essential role in improving patient outcomes, in part by helping to apply clinical guidelines for care. Management of COPD consists of reduction of risk factor exposure (for example, smoking cessation), influenza vaccination, pharmacotherapy, and pulmonary rehabilitation. Comorbidities may pose a special challenge in patients with COPD and they may compete with COPD for attention during office visits. Of particular note with regard to pharmacotherapy is the choice of delivery system. Handheld inhalers form the mainstay of treatment of COPD; however, some patients have difficulty using inhalers because of an inability to generate sufficient inspiratory flow, impaired manual dexterity, or cognitive impairment that leads to difficulties in following instructions concerning how to use the inhaler. In such patients, nebulization may be an effective alternative. In this review, we provide a list of best practices that can assist nurses in the optimal care of patients with COPD. Keywords: chronic obstructive pulmonary disease, exacerbation, long-acting beta-agonist, bronchodilators, nebulization